The Meaning of 'Refutation' in Kant's Refutation of Idealism - Hyoung Sung Kim (Journal of Modern Philosophy)
In his “Refutation of Idealism” Kant promises what he calls a “refutation [Widerlegung]” of Cartesian skepticism. There are many difficult questions concerning the Refutation. In this article, I focus on a question concerning the Refutation that, to my knowledge, has thus far escaped scrutiny: what does Kant mean, exactly, by a ‘refutation’? By examining Kant's legal, logical, and critical uses of 'refutation', I argue for what I call a ‘diagnostic’ reading of the Refutation: Kant seeks to identify the grounds for why someone might be attracted to Cartesian skepticism and then appeals to his doctrines concerning space and time in the Transcendental Aesthetic to show how such grounds contains a difficult-to-see error. In contemporary terms, Kantian 'refutations' resemble so-called ‘debunking arguments’ which seek to undermine a belief’s rational standing by characterizing the grounds for the belief in question as flawed, defective, or unfavorable.